Solubilization of ibuprofen by sucrose ester surfactants / Taufeq Hidayat Misdi - Misdi, Taufeq Hidayat (2013)
Different concentrations of sucrose laurate solution with constant amount of ibuprofen were prepared to study the effect of sucrose laurate surfactants on solubility of ibuprofen. A study on standard calibration curve of ibuprofen was conducted to determine the amount of ibuprofen dissolved. Uv-vis spectroscopy was used to analyze the solubility of ibuprofen in sucrose ester surfactants. The results proved that sucrose laurate can improved the solubility of ibuprofen.